Literature Review : Determinant of Latent Tuberculosis Infection (LTBI) in Developing Country - Radi, Radi; Firdaus, Dwiyan Maharani Mutiara (Insights in Public Health Journal, 2024)
Background: The problem of TB in Indonesia is increasingly worrying considering that Indonesia is the second country with the most TB cases in the world. Serious efforts are needed to break the chain of TB transmission as early as possible by focusing on preventing risk factors for transmission. TB transmission often occurs within the family, the vulnerable group being infected with TB who live in the same house as TB sufferers. The study aims to know the determinants of latent TB infection in children under 15 years old and adults in developing countries. Method: This study used the literature review method by collecting journals from Google Scholar, PubMed, and ScienceDirect. Data collection using keywords Risk Factors AND ILTB AND Developing Country. The results of the livelihood obtained a total of 125 articles which were then carefully selected so that 8 of the most relevant articles were obtained for article review. Results: The research results show that the determinants of ILTB infection are individual factors in the form of history of BCG vaccination, gender, age, history of contact with TB patients, marital status, duration of work, and protozoan infection. The second factor is socioeconomic factors in the form of home ownership, poverty and employment. The third factor is behavior which includes the habit of sleeping in the same room, smoking, sharing needles, and keeping animals at home. Conclusions: The determinants of ILTB infection are individual, behavioral and socioeconomic factors Keywords: Latent TB, Risk Factor, Developing Country